Application of technological processes to obtain pâté products with different non-commercial sizes, from Nile tilapia (Research, Society and Development, 2022)
During the harvesting process in excavated ponds, an expressive amount of tilapia outside the commercial standard size for slaughter in warehouses is observed, normally between 600 and 900 grams. These small fish are either sent to the settling ponds, or when they arrive mixed with other commercial-sized fish at the fish warehouses, they are sent to prepare co-products, such as flour, for example. With the objective of taking advantage of these non-commercial tilapia, samples of these fish were processed to obtain the clean trunk, canned, and smoked and later tests of acceptability and purchase intention of pâtés prepared with this processed fish were carried out. The tilapia were divided by weight into three treatments: Small (≥50g); Medium (51 to 80g); and Large (81 to 100g). The pates then prepared were subjected to sensory analysis of organoleptic attributes by 31 untrained evaluators. More than 87% of the evaluators liked the pâtés prepared with canned tilapia, and the indices of possibility of purchase and purchase of the canned were superior to 70%. It is concluded that these non-commercial-sized fish have great potential to generate by-products from the fish industry, due to the high acceptability, especially of canned products.